Political Marketing Prabowo Subianto and Sandiaga Salahuddin Uno in the 2019 Presidential Election - Bismar Harris Satriawan; Titin Purwaningsih (Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
This research explains how the political marketing of Prabowo Subianto and Sandiaga Salahuddin Uno was conducted in the 2019 presidential election. This study uses a qualitative approach, and data collection methods use in-depth interviews and documentation. The results showed that Prabowo-Sandiaga tried to maximize all stages of their political marketing concept, nevertheless the political marketing concept carried out by Prabowo-Sandiaga had not yet had a good impact on the final results in the 2019 presidential election. On the other hand, all the stages of the political marketing concept carried out by Prabowo-Sandiaga in the 2019 presidential election slightly increased the total votes if compared to the total votes obtained in the previous presidential election. The stages of political marketing carried out by Prabowo-Sandiaga in the 2019 presidential election started with Segmentation, Targeting, Positioning, and Political Marketing Campaign Strategy. Prabowo-Sandiaga has several political segmentations which are then given a focus on political targets with patterns full market coverage. Prabowo-Sandiaga has a positioning on issues such as: Welfare, Justice, Prosperity. The positioning strategy pattern used is the rationalization strategy. Political marketing campaign strategy carried out with push political marketing, pull political marketing, and pass political marketing.